Răspuns :
[tex] \frac{2}{3} (1 + \frac{3 - 7x}{2} ) = x[/tex]
[tex] \frac{2}{3} \times 1 + \frac{2}{3} \times \frac{3 - 7x}{2} = x[/tex]
[tex] \frac{2}{3} + \frac{2(3 - 7x)}{3 \times 2} = x[/tex]
[tex] \frac{2}{3} + \frac{6 - 14x}{6} = x \: | \times 6[/tex]
[tex]4 + 6 - 14x = 6x[/tex]
[tex] - 14x - 6x = - 4 - 6[/tex]
[tex] - 20x = - 10 \: | \div ( - 10)[/tex]
[tex]2x = 1[/tex]
[tex]x = \frac{1}{2} [/tex]
[tex] \frac{2}{3} \times 1 + \frac{2}{3} \times \frac{3 - 7x}{2} = x[/tex]
[tex] \frac{2}{3} + \frac{2(3 - 7x)}{3 \times 2} = x[/tex]
[tex] \frac{2}{3} + \frac{6 - 14x}{6} = x \: | \times 6[/tex]
[tex]4 + 6 - 14x = 6x[/tex]
[tex] - 14x - 6x = - 4 - 6[/tex]
[tex] - 20x = - 10 \: | \div ( - 10)[/tex]
[tex]2x = 1[/tex]
[tex]x = \frac{1}{2} [/tex]
aducem la același numitor fracțiile din paranteză
2/3[(2+3-7x)/2]=x
2(5-7x)/6=x
2(5-7x)=6x
10-14x=6x
20x=10
x=10/20
x=1/2